Design of Prodrugs and Their Functions in Cancer Treatment - Karagül, Esra; Soylu, Ozge (Atatürk Üniversitesi, 2024)
Prodrugs are inactive drug forms that are generated chemically modifications with the intention of increasing the availability of parent drugs. These drugs can be activated in vivo or inside the human body, despite being pharmacologically inactive. To ensure targeting or enhance the pharmaceutical, pharmacodynamic, and/or pharmacokinetic qualities of medications, prodrugs are derived from parent drug molecules. Enzymatic or non-enzymatic reactions of functional groups that provide derivatization are the means by which prodrugs are bioactivated. Targeting to the intended tissue can also be accomplished because the instruments used to produce bioactivation are specific to the target tissue. The prodrug approach is likewise relevant to the treatment of cancer because anticancer drugs have cytotoxic effects on healthy cells. Targeted prodrugs, which focus on tumor-specific features, allow for selective treatment and reduce damage to healthy cells. The theoretical framework of prodrugs was outlined in this paper, emphasizing on their significance, objectives, preparation methods, and targeting techniques, along with examples of prodrugs, along with examples of prodrugs. Additionally, the current research provided a summary of the usage and breadth of prodrugs in cancer treatment.

Ön ilaçlar, ana ilaçlardan yararlanma miktarını arttırmak için tasarlanan ve kimyasal modifikasyonlarla elde edilen inaktif ilaç formlarıdır. Bu ilaçlar, farmakolojik olarak inaktif olup in vivo ortamda ya da insan vücudunda aktive olabilmektedir. İlaçların farmasötik, farmakodinamik ve/veya farmakokinetik özelliklerini iyileştirmek veya hedeflemeyi sağlamak amacıyla ana ilaç moleküllerinden ön ilaçlar türevlendirilmektedir. Ön ilaçların biyoaktivasyonu, türevlendirmeyi sağlayan fonksiyonel grupların enzimatik veya non-enzimatik reaksiyona uğraması ile mümkün olmaktadır. Biyoaktivasyonu sağlayan araçların hedef dokuya spesifik olmasıyla istenen dokuya hedeflendirme de sağlanabilmektedir. Antikanser ilaçların sağlıklı hücrelere sitotoksik etki göstermesi sebebiyle ön ilaç stratejisi, kanser tedavisinde de ilgi görmektedir. Tümöre özgü özellikleri hedef alan ön ilaçlar sayesinde selektif bir tedavi sağlanabilmekte ve sağlıklı hücrelerin zarar görmesi azaltılmaktadır. Bu çalışmada, ön ilaçların kavramsal çerçevesi çizilerek önemi vurgulandı, amaçları, hazırlama yöntemleri ve hedefleme teknikleri ön ilaç örnekleri ile incelendi. Ayrıca ön ilaçların kanser tedavisindeki yeri ve kullanımı güncel araştırmalar ışığında özetlendi.
Ön İlaçların Tasarımı ve Kanser Tedavisindeki Fonksiyonları
Keywords: Molecular Medicine; Moleküler İlaç